Diseño y elaboración de material didáctico en kichwa para el aprendizaje de Ciencias Naturales en cuarto y séptimo año de Educación General Básica, en la Escuela Nazacota Puento de la parroquia El Sagrario, cantón Cotacachi - Guandinango Guandinango, Aida Verónica (2015)
In education is necessary to enrich the daily work with the use of teaching resources, because they are considered as curriculum support, helping the teacher to achieve their goals, allowing incorporate tools that innovate teaching practice and thus facilitate the student to better understand the issues raised in class. This paper presents two dimensional teaching resources for the area of Natural Sciences to be implemented with fourth and seventh year of basic general education school Nazacota Puento, the two materials are designed to work on soil, flora and fauna of our country.